DIVIDEND POLICY AS A MODERATOR IN THE EFFECT OF PROFITABILITY, LIQUIDITY, AND FIRM SIZE ON STOCK PRICES - Rahardian Nugroho Wicaksono; Muslimin (Universitas Tulungagung, 2026)
This study aims to analyze the effect of profitability, liquidity, and firm size on stock prices and to examine the role of dividend policy as a moderating variable in healthcare companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research applies a quantitative approach using secondary data obtained from annual financial reports and stock price data. The sample was selected using purposive sampling, resulting in 16 companies with 64 observations. The data were analyzed using descriptive statistics, classical assumption tests, and moderated regression analysis with SPSS 26. The novelty of this study lies in examining dividend policy as a moderator in the relationship between firm fundamentals and stock prices specifically within the healthcare sector, which exhibits unique post-pandemic characteristics. Unlike other sectors, healthcare companies face intensive capital needs for expansion and changing investor preferences toward long-term growth over short-term dividend yields, making the evaluation of dividend policy in this sector a unique empirical contribution. The results show that profitability affects stock prices, while liquidity and firm size have no effect. Dividend policy is unable to moderate the effect of profitability, liquidity, and firm size on stock prices. The implication of this study suggests that investors should prioritize profitability when evaluating healthcare stocks, while companies should strengthen their profit-generating ability.